Designing a Tourist Logo Inspired by the Folklore of Al-Qunfudhah Governorate of Saudi Arabia - Al Rashidi, Halima Mohammed Mishari; Al-Dabbagh, Maha Abdullah (Advances in Social Sciences Research Journal, 2022)
This study aimed to identify the concept of folklore, its significance, the role of tourism and culture and their impact on the economy. It also aimed at creating a tourist logo inspired by the Saudi folklore of Al-Qunfudah Governorate, and use the Saudi folklore in Al-Qunfudhah Governorate in designing the tourist logo. Another objective was to present a proposed tourism logo that contributes to encouraging the employment of folklore in designs. The researcher used the descriptive research which aims at casting light on current issues or problems through a process of data collection that enables them to describe the situation more completely than was possible without employing this method (Fox, 2007). The study has produced different tourist logos inspired by the Saudi folklore of Al-Qunfudah Governorate. The researchers have presented some recommendations as follows: Making use of heritage and historical sources in highlighting the national identity. Paying more attention to the design of tourism logos by researchers, because the tourism logo has a great role that no one else can perform, and the correct promotion process can only be done with it. Designing tourist souvenir products based on the logo to highlight the national identity of Al-Qunfudhah Governorate. Developing curriculum units for school students in various artistic fields to be concerned with preserving and documenting traditional folk arts. Conducting more studies and future research in the field of traditional folk arts, especially for Al-Qunfudhah Governorate.